The Church and Politics in Chile : Challenges to Modern Catholicism. - Smith, Brian H. (Princeton legacy library., 2014)
Clarifying the growing role of the Latin American Catholic Church as an agent of social change, Brian H. Smith discusses the prophetic function of the Chilean Church during the country's metamorphosis from Conservative to Christian Democratic to Marxist to repressive military regime. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important bo.